Seminar parenting: Peran orang tua terhadap pembentukan karakter anak di Desa Ngebruk - Cielo, Esperanza (Maliki Interdisciplinary Journal, 2025)
The parenting seminar titled "The Role of Parents in Shaping Children's Character" was organized by Group 10 KKM UIN Malang on January 9, 2025, in Ngebruk Village, Poncokusumo, Malang Regency. This seminar aimed to raise parents' awareness of the importance of character-based parenting in developing strong and ethical children. Dr. Hj. Rofiqah, M.Pd., C.Ht., presented various practical strategies for parents, including building healthy communication, understanding children's emotional needs, and managing the impact of technology on their development. Interactive discussions and Q&A sessions allowed participants to share experiences and find solutions to modern parenting challenges. The seminar results indicate that proper parenting education can help parents shape children's character more effectively. It is hoped that similar programs will continue to be conducted to enhance understanding and collaboration between parents, teachers, and the community in supporting children's holistic development.